Political Dynasty and Single Candidate in Indonesian Local Elections: Where Are The Parties? - Zaldi Rusnaedy; Fatma Fatma; Almuhajir Haris (Universitas Pancasakti, 2021)
The pragmatism of political parties is one of the causes for the proliferation of political dynasties and the massive number of single candidates in several electoral politics periods at the local level. The implementation of the 2020 local election simultaneously gave birth to many candidates who have a kinship with political officials both at the central and regional levels, both currently or who have served. Apart from the practice of dynastic politics, a single candidate's presence also adds to the problems in the democratic process at the local level. A single candidate is present as a consequence of implementing the local election system simultaneously, which opens wide the opportunity for the local election to be held even though only one pair of regional head candidates are joined, as a consequence, the empty column is presented as the opponent of the match. This article collects data through a literature study. To answer these two phenomena, the author examines them during the local election implementation. This study indicates that these two phenomena co-opt local democracy and clog the circulation of the leadership elite. Both political dynasty candidates and single candidates have enormous potential to win elections. Both phenomena are caused by poor internal recruitment and candidate selection processes.